Monopsony and the Lifetime Relation between Wages and Productivity - Ioannides, Yannis M.; Pissarides, Christopher A. (Journal of Labor Economics, 1985)
We consider the relation between wages and productivity by means of a model based on the following assumptions. Workers live for 2 periods, firms live forever, senior workers differ nontrivially from junior, seniority enhances workers' expected second-period earnings, both firms and workers recognize the prospect of promotion and the senior-junior wage differential at the time of hiring, and firms have monopsony power in hiring junior workers. We show that senior wages are equal to the senior marginal product, but junior wages are set below the junior marginal product by an amount that depends on the elasticity of the firm's labor supply.